2014
DOI: 10.15388/informatica.2014.13
|View full text |Cite
|
Sign up to set email alerts
|

On the Optimization of Investment Strategies in the Context of Virtual Financial Market by the Individual Approach to Risk

Abstract: The optimal financial investment (Portfolio) problem was investigated by leading financial organizations and scientists. Nobel prizes were awarded for the Modern Portfolio Theory (MPT) and further developments. The aim of these works was to define the optimal diversification of the assets depending on the acceptable risk level.In contrast, the objective of this work is to provide a flexible, easily adaptable model of virtual financial markets designed for the needs of individual users in the context of utility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…While the performance of sharia-based investment instruments is not significantly different from conventional investment instruments, during the research period, Islamic investment instruments showed slightly better performance (Syafrida et al, 2014). Mockus et al (2014), the author, provided that the minimal prediction errors do not provide the maximal profits. In a company's risk profile, Hudakova & Dvorsky (2018) said that the biggest risk in a company is market risk, financial risk, and economic risk.…”
Section: Descriptive Statisticsmentioning
confidence: 95%
“…While the performance of sharia-based investment instruments is not significantly different from conventional investment instruments, during the research period, Islamic investment instruments showed slightly better performance (Syafrida et al, 2014). Mockus et al (2014), the author, provided that the minimal prediction errors do not provide the maximal profits. In a company's risk profile, Hudakova & Dvorsky (2018) said that the biggest risk in a company is market risk, financial risk, and economic risk.…”
Section: Descriptive Statisticsmentioning
confidence: 95%